Alpha Lactose Monohydrate Morphology: Molecular Modelling and Experimental Approach - Lukman, Zulfahmi; Anuar, Nornizar; Fitrah Abu Bakar, Noor; Abdul Rahman, Norazah (International Journal of Engineering and Technology, 2018)
This study is conducted to investigate morphologies ofalpha lactose monohydrate (Î±LM) grown in polyethylene glycol 300 (PEG 300) solution and vacuum condition via molecular modelling techniques. Surface chemistry of predicted Î±LM is described. The molecules of Î±LM in its unit lattice were optimized prior to morphological prediction of attachment energy method and the suitable potential function was determined. The predicted lattice energy of Î±LM was in excellent agreement with the experimental lattice energy with percent errors of 3.9%. The morphology of Î±LM is predicted to be hexagonal in shape, similar to crystal morphology of Î±LM grown in PEG 300 solutions. It was found that the lattice energy and of Î±LM was dominated by the weak van der Waals force.Â Â